TRANSFORMASI BAHAN ALAM MENJADI MEDIA BALOK EDUKATIF: SOLUSI KETERBATASAN FASILITAS PEMBELAJARAN SPASIAL DI TK NURUL HUDA ARSO 11: Transformasi Bahan Alam Menjadi Media Balok Edukatif: Solusi Keterbatasan Fasilitas Pembelajaran Spasial di TK Nurul Huda Arso 11 - Hermasyah Hermansyah (Al-Thifl: Jurnal Pendidikan Anak Usia Dini, 2026)
This study aims to examine the construction of visual–spatial intelligence in early childhood through block play within a learning-center setting at TK Nurul Huda Yapis Arso 11. Visual–spatial intelligence is understood as children’s ability to perceive, manipulate, and visualize relationships among objects in three-dimensional space, which is a crucial foundation for cognitive development and academic readiness. This research employed a descriptive qualitative approach, with data collected through participatory observation, in-depth interviews, and documentation. The research subjects included kindergarten children, classroom teachers, and the use of local resources as alternative block-play materials. Data analysis was conducted through data reduction, data display, and conclusion drawing, while triangulation techniques were applied to ensure the trustworthiness of the findings. The results indicate that thematically designed block play, supported by careful teacher preparation, enhances children’s ability to recognize shapes, sizes, colors, and spatial relationships in a concrete manner. Furthermore, block play positively contributes to children’s creativity, problem-solving skills, fine motor coordination, and social interaction during play activities. Supporting factors include teacher creativity, a safe and conducive learning environment, and the utilization of local materials as learning media. Meanwhile, the main challenges identified were limited facilities and children’s difficulties in sharing play materials. This study concludes that block play in a learning-center setting is an effective and sustainable instructional strategy for developing visual–spatial intelligence in early childhood education, particularly in early childhood institutions with limited resources. Keywords: Visual–Spatial Intelligence, Block Play, Early Childhood Education, Learning Centers, Play-Based Learning.